Comparison of ultraviolet radiation/hydrogen peroxide, Fenton and photo-Fenton processes for the decolorization of reactive dyes - Radović Miljana D.; Mitrović Jelena Z.; Kostić Miloš M.; Bojić Danijela V.; Petrović Milica M.; Najdanović Slobodan M.; Bojić Aleksandar Lj. (Hemijska Industrija, 2015)
The effectivness of UV/H2O2 process, Fenton and photo-Fenton process at decolorization of commercially important textile dyes Reactive Orange 4 (RO4) and Reactive Blue 19 (RB19) was evaluated. The effect of operational condition such as initial pH, initial H2O2 concentration, initial Fe2+ concentration and initial dye concentration on decolorization of RO4 and RB19 was studied. The photo-Fenton process is found to be more efficient than UV/H2O2 and Fenton process for decolorization of simulated dye bath effluent and solutions of the dyes in water alone under optimum conditions. In simulated dye bath the removal efficiency was slightly lower than for the solutions of the dyes in water alone for both dyes types. The results revealed that the tested advanced oxidation processes were very effective for decolorization of RO4 and RB19 in aqueous solution. [Projekat Ministarstva nauke Republike Srbije, br. TR34008]